The relationship between stride rates, lengths and body size and their affect on elite triathletes` running performance during competition - Landers, G. J.; Blanksby, B. A.; Ackland, T. R. (International Journal of Exercise Science, 2011)
Previous research has suggested that a degree of predictability exists in the relationship between self-selected running stride rates (SR) and stride lengths (SL) with measures of body size such as mass, height and limb lengths. Significant correlations have also been revealed between these body size measures and performance and between SL and performance. However, there is also evidence to suggest that triathlon performance may be related to maintaining a longer SL during the final run. Hence, the aim of this investigation was to examine whether there was any relationship between SR and SL, with body masses and heights of senior elite triathletes during the run stage of a triathlon. The SRs and SLs of 37 male senior elite Triathlon World Championships competitors were analysed via videography and Video Expert II Coach. These values were correlated with the athletes` body masses and heights (p<0.01). The results indicated a limited relationship between height and mass with SR in the early stages of the run. However, a significant, positive correlation existed between SL and height at all points from 3 km to the end of the run. Those triathletes who were taller used longer strides. Further research is warranted to examine the effects of cycling on the subsequent run discipline during triathlon and if body size and shape of triathletes have evolved as the young sport of triathlon develops.